Determination of heat input impact on residual stress, microstructure and mechanical characteristics of welded ferrite-pearlite (α-P) steel joints by using taguchi optimization approach - Nagaraju Doredla; Senthil Kumar N (Journal of Advanced Joining Processes)
Ferrite-Pearlite (α-P) steels like E350 steel were extensively used in pre-engineered structures like industrial warehouses, bridges, etc., owing to their special ductility property. Submerged arc welding is highly efficient in welding long-span prefabricated structures. In this paper, weld overlay and butt weld experimental investigations were performed to optimise the welding process by understanding the influence of heat input on residual stress generation, weld efficiency, microstructural and mechanical characteristics of the weld joint to match the filler wire with the base material characteristics. Trail runs were conducted using the Taguchi design optimisation approach. Taguchi method is useful to standardise and simplify the use of design of experiments. The weld quality was evaluated using non-destructive evaluations. Residual stress was tensile near the weld and transitioned to compressive further from the root. The intensity of residual stress decreased gradually with an increase in transverse distance from the weld root. Acicular ferrite, polygonal ferrite, and traces of lath bainite microstructure were observed in the weld zone. The weld microstructure became coarser toward the melting boundary of the welded joint with an increase in heat input greater than 1.09 kJ/mm. A notable decrease in weld brittleness was observed with an increase in heat input from 1.09–1.37 kJ/mm, and the fracture initiated away from the weld with ductile and quasi-ductile cleavages. The overall microstructure and mechanical characteristics of the welded joint were improved at a controlled heat input of 1.09–1.37 kJ/mm.